Knowledge and Scholarly Authority in Al-Ghazali’s Philosophy: A Study of Fatihatul ‘Ulum - Suwarno, M. Hadi; Albab, Hayyan Ahmad Ulul (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
Islamic education is a place to form humans who can carry out their duties as caliphs on earth. Knowledge of the concepts of science and scholars is needed to understand and develop science and scholars in Islamic teachings combined with the philosophy of Islamic education. This concept is the basis for understanding the philosophy of Islamic education. The two have a close relationship. The purpose of this research is to describe the concept of science according to Imam Al-Ghazali and to find out the role of ulama' according to Imam Al-Ghazali in the book of Fatihatul 'Ulum. This research method uses a literature review focused on the book of Fatihah al-Ulum. The data collection technique uses the documentation method related to the book of Fatihah al-Ulum and other works that are still one theme of discussion. Analysis of this literature study uses content analysis by looking at the validity of the original data and explaining it again by comparing other sources. First, researchers found knowledge as the main foundation of a person so that he can know Allah SWT. Studying science is considered something with good intentions by seeking the pleasure of Allah SWT. After knowledge is obtained, a person will become more moral and can practice religious and general knowledge with a heart that is always linked to Allah SWT. Secondly, being an ulama' is a big responsibility because he is the heir of the Prophet SAW. Ulama' must link their hearts to seek the pleasure of Allah, leave the affairs or desires of the world, and teach all the knowledge they have so that their students can take the path of Allah's pleasure.